2020
DOI: 10.22159/ijpps.2020v12i4.36707
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Doxorubicin and Doxorubicinol in Dried Blood Spot of Breast Cancer Patients for Monitoring the Cardiotoxicity of Doxorubicin

Abstract: Objective: This study aimed to analyze doxorubicin and doxorubicinol levels in Dried Blood Spot (DBS) from 25 breast cancer patients who received doxorubicin in their therapeutic regiment. Methods: DBS samples were extracted by protein precipitation method and analyzed using Ultra Performance Liquid Chromatography tandem Mass Spectrometry (LC-MS/MS), with the Acquity UPLC BEH C18 Waters chromatography column (2.1 x 100 mm x 1.7 μm). The mobile phase consisted of 0.1% acetic acid (eluent A) and acetonitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Clinical studies have confirmed this issue. Cardiomyopathy, gastrointestinal (GI) side effects and hematological abnormalities result from using DOX alone or in combination with other chemotherapeutic agents in cancer therapy [23][24][25]. Increased level of oxidative stress and subsequent apoptosis induction are responsible for DOX toxicity [26].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have confirmed this issue. Cardiomyopathy, gastrointestinal (GI) side effects and hematological abnormalities result from using DOX alone or in combination with other chemotherapeutic agents in cancer therapy [23][24][25]. Increased level of oxidative stress and subsequent apoptosis induction are responsible for DOX toxicity [26].…”
Section: Introductionmentioning
confidence: 99%
“… * Test solution and Found using −log [DOX] mol L −1 ** SE (%Error) = %RSD/ . *** The tabulated values of “ t -test” and ‘‘F-test’’ at confidence level p = 0.05 [ 52 ]. …”
Section: Resultsmentioning
confidence: 99%
“…A confirming study was performed by comparing the outcomes by other results obtained from a previously addressed method [ 52 ]. The random detection of plasma samples revealed that the modified DOX-PM-NiO/MgO nanocomposite sensor showed ultrasenstivity for the determination of DOX in bio samples rather than the previously reported method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations